Battery energy storage selection based on a novel intermittent wind speed model for improving power system dynamic reliability - Liang, Chen (2020)
Owing to intermittency of wind power and slow ramp rates of conventional generators, a considerable amount of wind energy cannot be effectively utilized during frequency control processes. This paper proposes a technique for power system planners and operators to select or commit power capacity and energy capacity of battery energy storage system (BESS) for mitigating the effects of intermittent wind speeds on reliability and economics. A novel procedure is proposed to determine intermittent wind speeds based on the chaos theory and intermittency-related parameters. The frequency-related reliability and economic indices of a power system with BESS are formulated based on frequency control processes. The effects of BESS on dynamic reliability and economics of a practical power system are investigated using the proposed techniques and models.